2007
DOI: 10.1159/000099208
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal Muscle of Female Rats Exhibit Higher Mitochondrial Mass and Oxidative-Phosphorylative Capacities Compared to Males

Abstract: The effect of gender and caloric restriction on mitochondrial content and oxidative-phosphorylative capacities has been investigated in rat gastrocnemius muscle. Muscle protein, mitochondrial protein and DNA contents, enzymatic activities of mitochondrial oxidative and phosphorylative system, mitochondrial antioxidant enzymes, protein levels of complex IV (subunit I and IV) and ATPase, and the gene and protein expression of mitochondrial transcription factor A (TFAM), involved in mitochondrial replication and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
63
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(76 citation statements)
references
References 45 publications
12
63
1
Order By: Relevance
“…These results support a role of E 2 in the sexual dimorphism in rat skeletal muscle that we have previously reported, whereby female rats show higher mitochondrial mass, greater oxidative capacity, and also a better antioxidant response than their male counterparts (Colom et al 2007a, Gó mez-Pérez et al 2008, 2012. Furthermore, we demonstrate that ovarian hormones play a relevant role in adiponectin synthesis in skeletal muscle, and that E 2 could be a key effector in the stimulation of skeletal muscle adiponectin sensitivity.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…These results support a role of E 2 in the sexual dimorphism in rat skeletal muscle that we have previously reported, whereby female rats show higher mitochondrial mass, greater oxidative capacity, and also a better antioxidant response than their male counterparts (Colom et al 2007a, Gó mez-Pérez et al 2008, 2012. Furthermore, we demonstrate that ovarian hormones play a relevant role in adiponectin synthesis in skeletal muscle, and that E 2 could be a key effector in the stimulation of skeletal muscle adiponectin sensitivity.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have reported that skeletal muscle of female rats shows greater mitochondrial differentiation and content accompanied by a higher OXPHOS capacity and better antioxidant response than that of males, which could explain the greater capacity of females to adapt to altered metabolic energy situations (Colom et al 2007a, Gó mez-Pé rez et al 2012. In addition, this sexual Tfam, mitochondrial transcription factor A; Nrf1, nuclear respiratory factor 1; Sirt1 and 3, sirtuin 1 and 3; MFN1 and 2, mitofusin 1 and 2; OPA1, optic atrophy protein 1; DRP1, dynamin-related protein 1.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Mitochondrial proteins did not comprise more than a third of total proteins identified, and did not show a blanket expression increase in one gender, leaving no evidence of a greater mitochondrial concentration in females. While females are thought to have a greater mitochondrial density than males [11], these studies use muscle tissue that has been metabolically challenged. Fig.…”
Section: General Protein Localization and Ontological Groupingmentioning
confidence: 99%